2016
DOI: 10.3390/ijerph13070743
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors in Psoriasis: The Point of View of the Nutritionist

Abstract: Psoriasis is a common, chronic, immune-mediated skin disease with systemic pro-inflammatory activation, where both environmental and genetic factors contribute to its pathogenesis. Among the risk factors for psoriasis, evidence is accumulating that nutrition plays a major role, per se, in psoriasis pathogenesis. In particular, body weight, nutrition, and diet may exacerbate the clinical manifestations, or even trigger the disease. Understanding the epidemiological relationship between obesity and psoriasis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 86 publications
2
95
0
1
Order By: Relevance
“…W kilku badaniach potwierdzono, że pacjenci z łuszczycą spożywają większe ilości cukrów prostych, tłuszczów, n-6 PUFA i kalorii, a mniej białek, węglowodanów złożonych, MUFA, n-3 PUFA i błonnika. Nieprawidłowe nawyki żywieniowe korelowały z występowaniem otyłości, cięższym przebiegiem łuszczycy i obniżeniem jakości życia [80][81][82][83]. W najnowszym badaniu opartym na kwestionariuszu Afifi i wsp.…”
Section: Dieta W łUszczycyunclassified
See 1 more Smart Citation
“…W kilku badaniach potwierdzono, że pacjenci z łuszczycą spożywają większe ilości cukrów prostych, tłuszczów, n-6 PUFA i kalorii, a mniej białek, węglowodanów złożonych, MUFA, n-3 PUFA i błonnika. Nieprawidłowe nawyki żywieniowe korelowały z występowaniem otyłości, cięższym przebiegiem łuszczycy i obniżeniem jakości życia [80][81][82][83]. W najnowszym badaniu opartym na kwestionariuszu Afifi i wsp.…”
Section: Dieta W łUszczycyunclassified
“…On the other hand, they eat less proteins, complex carbohydrates, MUFA, n-3 PUFAs and dietary fibre. Inappropriate eating habits have exhibited a correlation with obesity, more severe course of psoriasis and impairment in the quality of life [80][81][82][83]. In the most recent questionnaire-based study, Afifi et al assessed the eating habits of patients with psoriasis.…”
Section: Diet In Psoriasismentioning
confidence: 99%
“…The Mediterranean diet (Barrea et al, ) is a dietary pattern characterized by: (a) High intake of extra virgin olive oil, fruits, vegetables, legumes, cereals, fish, and seafood; (b) Low intake of dairy products, meats, and derivatives; and (c) consumption of moderate amounts of alcohol during the meal in the form of wine. It is a source of antioxidants and monounsaturated fatty acids compounds with anti‐inflammatory properties that are associated with a lower cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet is a healthy diet it is characterized by a high intake of fruit and vegetables, legumes, grains and cereals, fish and seafood, and nuts; a low intake of dairy products, meat and meat products; and a moderate ethanol intake mainly in the form of wine and during meals. Extra virgin olive oil (EVOO) is the main added lipid and its increased consumption is reflected in the high monounsaturated to saturated fatty acid intake [28,29]. However, there are few studies that relate to the Mediterranean diet with psoriasis.…”
Section: Fish Oil and Psoriasismentioning
confidence: 99%
“…Recent evidence has confirmed that adherence to a healthy diet over time reduces the risk of long-term inflammation [28]. The antioxidants present in the diet, such as omega-3 from fish oil, some vitamins (A, E, and C), and oligoelements (iron, copper, manganese, zinc, and selenium), which decrease oxidative stress and the production of reactive oxygen species, might be of particular relevance mainly in a chronic systemic inflammatory diseases, like psoriasis [29].…”
Section: Fish Oil and Psoriasismentioning
confidence: 99%